Investasi Bagi Hasil di Bank Syariah: Perspektif Akuntansi - Rijal Allamah Harahap; Saparuddin Siregar (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study was to examine the accounting treatment for mudharabah contracts and their implications for the reliability and fairness of financial statements based on an accounting perspective in Islamic banks. In addition, this study also explores the effect of provisions and reserves on profit allocation among profit-sharing investment account holders (mudharabah) and examines the accounting treatment for mudharabah contracts as stated in the Accounting Standards for Islamic Financial Institutions issued by AAOIFI. The findings of this study that presenting customers in a separate category in the statement of financial position (balance sheet), without reclassifying assets in the statement of financial position to reflect assets attributable to customers, indicates an undue bias in the financial statements. This goes against the concept of full disclosure and a true and fair view of financial statements. Other results also reveal that reserves can result in misallocation of profits among customers and there is an overlap between provisions and reserves, which can affect the reliability and fairness of financial statements. It is also revealed that the reserves presented under the customer section cannot be easily understood because investors do not have rights to these reserves. In addition, questioning the application of the use of grant contracts (Tabarru) in transactions with the substance seeking profit. This study recommends mutual funds as a solution for implementing sharia-compliant mudharabah contracts.